P.095 Clinical outcomes following carotid angioplasty and stenting in patients over age of 75: Careful patient selection overcoming the age-effect. (17th June 2016) - Alizadeh Vakili, N; Drake, B; Bharatha, A; Chiu, A; Marotta, T; Montanera, W; Sarma, D; Spears, J
Abstract : Background: CAS is reported to have higher complication rates in elderly compared to younger patients. This effect may be a surrogate for unfavourable anatomy (tortuosity, arch/access vessel atheroma burden) for endovascular treatment. We report our experience with 42 highly selected patients with favourable anatomy in spite of age.Methods: From a cohort of 217 consecutive patients undergoing CAS at St Michael's Hospital from 2010-2016, stroke and a composite outcome of stroke, MI or death at 30 days post procedure was recorded. We compared outcomes in patients below and above the age of 75.Results: In 217 patients, 175 (80.7%) were below and 42 (19.3%) were above age 75 years. The stroke rate was 1.7% (n=3) and 2.4% (n=1), for patients below and above age 75 years respectively (p=0.58). The composite outcome rate was 4.0% (n=7) and 4.8% (n=2) for patients below and above age 75 years respectively (p=0.69).Conclusions: Patients without high-risk anatomic features were selected for CAS treatment. In this selected group, outcomes for those older than 75 years are comparable to the younger age category. Complication rates were comparable to the results in major randomized symptomatic carotid trials.